Proceedings of the 9th ACM SIGPLAN International Workshop on Virtual Machines and Intermediate Languages 2017
DOI: 10.1145/3141871.3141872
|View full text |Cite
|
Sign up to set email alerts
|

Cross-ISA debugging in meta-circular VMs

Abstract: Extending current Virtual Machine implementations to new Instruction Set Architectures entails a significant programming and debugging effort. Meta-circular VMs add another level of complexity towards this aim since they have to compile themselves with the same compiler that is being extended. Therefore, having low-level debugging tools is of vital importance in decreasing development time and bugs introduced. In this paper we describe our experiences in extending Maxine VM to the ARMv7 architecture. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Recently, the team of Maxine reported a QEMU test-based infrastructure for cross-ISA testing and debugging [13]. They reported that this infrastructure helped them in porting their VM to AArch32 (ARMv7), similarly that what ours helped us in porting to AArch64.…”
Section: Related Workmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, the team of Maxine reported a QEMU test-based infrastructure for cross-ISA testing and debugging [13]. They reported that this infrastructure helped them in porting their VM to AArch32 (ARMv7), similarly that what ours helped us in porting to AArch64.…”
Section: Related Workmentioning
confidence: 87%
“…For example, it has been reported that debugging memory corruption bugs in a simulation could take several hours of execution 1 . Recently, the team of Maxine recently reported a test-based infrastructure for cross-ISA debugging [13]. They report that still debugging happens in gdb in a different abstraction level than the original source code and that they are not able to cover many parts of their codebase.…”
Section: Introductionmentioning
confidence: 99%
“…VM Testing. Maxine and Pharo reported recently QEMU based unit testing infrastructures for cross-ISA testing and debugging [15,25]. They reported that this infrastructures helped them in porting their VMs to ARMv7 and ARMv8 64bits respectively.…”
Section: Related Workmentioning
confidence: 99%
“…For example, it has been reported that debugging memory corruption bugs in a simulation could take several hours of execution 1 . Recently, the team of Maxine reported a test-based infrastructure for cross-ISA debugging [15]. They reported that most debugging happens in gdb when bootstrapping a new architecture, in a different abstraction level than the original source code, and that they were not able to cover many parts of their codebase.…”
Section: Introductionmentioning
confidence: 99%
“…In order to support multiple ISAs, MaxineVM and its compilers are being ported to different architectures. Currently, Beehive executes on x86 and ARMv7 architectures while ongoing work extends the support for AArch64 and RISC-V via the CrossISA toolkit [14].…”
Section: The Beehive Ecosystemmentioning
confidence: 99%